River conservation and management - Boon, Philip J.; Raven, Paul J. (Wiley-Blackwell, 2012)
This title provides an overview of how changes in legislation, policies, institutional responsibilities, science, technology, practical techniques and public perception have influenced how rivers have been managed over the past 20 years and the challenges that lie ahead during the next 20 years.